Utilisation des marqueurs microsatellites pour l'étude des contributions parentales chez l'huître creuse Crassostrea gigas - Boudry, Pierre; Collet, Bertrand; Kotoulas, G.; Hervouet, Veronique; Cornette, Florence; Bonhomme, Francois; Gerard, Andre (Présentation Journées Conchylicoles, Ifremer Nantes, 24-25 mars 1999, 1999)
Numerous aquacultural species show very high fertilities. As a consequence, it is possible to produce, in hatcheries, a large amount of sibs from a small amount of parents. The sibs' genetic variability is, of course, directly linked to the number of parents involved, but it may be largely lowered by imbalanced parental contributions. Polymorphic genetic markers are very handy tools in the study of these phenomena in cultivated populations (Harris et al. 1991; Herbinger et al., 1996a; Garcia de Leon et al. 1998) or in natural populations (Ferguson et al, 1995; Kellog et al., 1995; Colbourne et al., 1996; Herbinger et al., 1996b). This document is a presentation of the results of a number of experiments, realised in the scope of the European program "GENEPHYS", and using microsatellite markers to analyse the parental contributions in the flat oyster Crassostrea gigas in vitro crossbreeding. The relatedness analysis was made easier by the large polymorphism observed in the four studied loci. Thus, in a crossbreeding involving 20 males and 20 females, the father or mother of a quarter of the sibs could be determined with only one microsatellite locus presenting 28 alleles. In crossbreedings involving 5 males and 5 females, each sib could be assigned to a family using 3 loci. In every case, the combination of 2 loci genotypes enabled the identification of the parents. Despite balanced parental gametic contributions at the time of fertilization, unbalanced parental contributions are observed in sibs, during larval and juvenile stages. In order to identify the causes of those imbalances, the effects of the zygotic and gametic competition have been studied, comparing different types of crossbreeding (with or without gametic competition) at different stages of their development. De nombreuses espèces aquacoles présentent de très fortes fécondités. Il est donc possible, dans les écloseries, de produire de très grands nombres de descendants à partir d'un nombre réduit de parents. La variabilité génétique des descendants ...